2017
DOI: 10.1186/s41241-017-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

The roles of miRNAs in human breast cancer and canine mammary tumor

Abstract: MicroRNAs have become a hot topic in cancer research nowadays due to their important role not only on cancer development, progression, invasion but also on repression of cancer related genes. With advanced technologies, these microRNAs can easily be detected from biopsy samples and blood for early diagnosis, prognosis and treatment. Due to increasing demand of research in exploring expression profile of microRNAs with respect to different subtypes of breast cancer, this review aimed to provide an update on mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…In the nucleus, the RNA polymerase II transcribes non-coding miRNA gene into 100-120 nt long hair pin structured primary-miRNA (pri-miRNA) (Petri and Klinge, 2020;Lee et al, 2004;Yu and Cheah, 2017) (as shown in Fig. 1).…”
Section: Biosynthesis Of Mirnamentioning
confidence: 99%
See 2 more Smart Citations
“…In the nucleus, the RNA polymerase II transcribes non-coding miRNA gene into 100-120 nt long hair pin structured primary-miRNA (pri-miRNA) (Petri and Klinge, 2020;Lee et al, 2004;Yu and Cheah, 2017) (as shown in Fig. 1).…”
Section: Biosynthesis Of Mirnamentioning
confidence: 99%
“…Liang et al, 2018;Liu et al, 2018;Santolla et al, 2018;Zong et al, 2019;Chen et al, 2020;Tang et al, 2019 Cluster 17/20 (miR-17-3p, miR-17-5p, miR-18, miR-19a, miR-19b, miR-20, and DNA damage; cell proliferation; drug resistance; FOXM1/eEF2K signaling axis Li et al, 2013;Christoffersen et al, 2010;Welch et al, 2007;Sun et al, 2008;Bayraktar et al, 2018;Lin et al, 2017;Rui et al, 2018 miR-200 BMI-1, ZEB1, ZEB2, QKI, MYB TGF-β signaling; EMT process; tamoxifen resistance Uhlmann et al, 2010;Cochrane et al, 2010;Gregory et al, 2008;Dykxhoorn et al, 2009;Shimono et al, 2009;Kim et al, 2019;Gao et al, 2019 (Continued ) Dicer is a RNase III class of enzyme that cleaves the hair pin region of pre-miRNA to produce 20-30 nts of duplex miRNA composed of two single guide (5' to 3') and passenger (3' to 5') strands (Kobayashi and Tomari, 2016;Höck and Meister, 2008;Petri and Klinge, 2020). This guide strand joins the PAZ domain of RNA-induced silencing complex (RISC) to mediate post-transcriptional gene silencing of the target mRNA through Argonaute 2 (AGO2, RNase, catalytic part of RISC having "slicer" activity) which cleaves the target mRNA and the PIWI domain of RISC is responsible for the degradation of passenger strand (Höck and Meister, 2008;MacFarlane and Murphy, 2010;Yu and Cheah, 2017).…”
Section: Biosynthesis Of Mirnamentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-93 may be a biomarker linked to TNBC's biological and clinical characteristics (155). Micro-RNAs can help in early diagnosis, prognosis, and effective treatment for human breast cancer and canine mammary tumor (156). MicroRNA-10b, miR-15a, miR-19a, miR-26b, miR-30a, miR-30c, miR-125a, miR-125b, miR-148a, miR148b, miR-195 and miR-320 are down-regulated both in dogs and in humans while miR-494 is upregulated in both species (157).…”
Section: Exosomes and Mirnasmentioning
confidence: 99%
“…Mammary gland neoplasms exhibit several similarities between women and dogs, such as their high incidence, spontaneous appearance, common environmental risk factors, hormone receptor expression and neoplastic growth markers. Therefore, research related to one species may have aspects that can be studied in a comparative manner [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%